Lesson Learn from Traditional-Vernacular Houses in Kinali Village, West Lampung, Indonesia - Siregar, Andi Harapan (Universitas Komputer Indonesia, 2023)
Traditional-vernacular housings are customarily built to meet the specific needs, values, and ways of living of the local people within a specific environmental context and resources. They are unique compared to other kinds of housings currently in use by the society because they are non-engineered construction and transferred by the ancient tradition so that they could withstand its physical environment and be easily accepted by the local people. The uniqueness is called indigenous knowledge or local wisdom. Indonesia is a country that consists of traditional-vernacular housings in various places. This paper will elaborate on one of the traditional-vernacular housing in Indonesia, which are traditional-vernacular housings in Lampung. The purposes of this research are to elaborate documentation of the indigenous’ knowledge of the traditional-vernacular housings in Lampung to apply for construction today. This paper is based on research which is purely field research and semistructured interview with various stakeholders of the traditional-vernacular housings and local community in Lampung. Field research and semistructured interviews focus on two aspects of observations, which are: 1) traditional building, and 2) skill & local resource use. Observation of traditional buildings include 1) house form & design, 2) structure system, 3) material used, 4) joinery & other details. Observation to skills and local resource use include: 1) building skill, and 2) culture (such as solidarity)